Accuracy of Computed Tomography Attenuation Values in Differentiating Transudative from Exudative Pleural Effusion (Nepalese Journal of Radiology, 2025)
Introduction: Pleural effusion, the accumulation of fluid between the lungs and chest wall, arises from various diseases. Differentiating transudative from exudative effusions is essential for diagnosis and management. While thoracentesis is the standard, CT offers a non-invasive alternative. This study assesses the accuracy of CT attenuation values in distinguishing effusion types.Methods: A single-center cross-sectional study was conducted at the Radiology Department, Patan Academy of Health Sciences, over one year. Patients with pleural effusion who underwent CT and thoracentesis within 48 hours were included. CT scans (Philips Ingenuity Core 128) measured attenuation values in Hounsfield Units (HU). Effusions were classified using Light’s criteria, and diagnostic performance was evaluated with ROC analysis to determine optimal cut-off values.Results: Among 137 patients, 41 (29.9%) had transudative and 96 (70.1%) had exudative effusions. Mean attenuation values were 7.66±3.22 HU for transudative and 10.75±3.80 HU for exudative effusions, with a significant difference (P=0.00001). ROC analysis identified 10.6 HU as the optimal cut-off, with 55.2% sensitivity, 87.8% specificity, 91.3% positive predictive value, and 45.5% negative predictive value. Features like pleural nodules, thickening, and loculations were not significantly differentiators (p>0.05).Conclusions: CT attenuation values offer a significant, specific, non-invasive method for distinguishing effusion types, beneficial for patients contraindicated for thoracentesis. Sensitivity remains moderate, but CT is a valuable diagnostic tool.